Model Pertanian Terpadu Tanaman Hortikultura dan Ternak Sapi untuk Meningkatkan Pendapatan Petani - L Siswati; R Nizar (Universitas Andalas, 2012)
Research was conducted to identify the diversity of technologies in an integrated farming system for horticulture and beef cattle. Furthermore, it observed the improving of farmer income that used this model. There were primary and secondary data with the survey method for farmers in Pekanbaru. The result showed the integrated farming system kept up to 21 heads of beef cattle and 4,22 ha of holticultures. Every farmer had around 0,3 ha farmland and approximately 4 to 5 heads of beef cattle. Finally, the integrated farming system increased the farmer income about Rp 9.731.147 per cultivating period of holticultures and about Rp. 9.345.328 per year of keeping the beef cattles.